Effect of AnnexinA Group Translocated in Extracellular Vesicles on Tumorigenesis - Wu, Qionghui; Wei, Haidong; Meng, Wenbo; Xie, Xiaodong; Zhang, Zhenchang; Su, Gang (Current Molecular Medicine, 2021)
Annexin, a calcium-dependent phospholipid-binding protein, can affect tumor cell adhesion, proliferation, apoptosis, invasion and metastasis, as well as tumor neovascularization in different ways. Recent studies have shown that annexin exists not only as an intracellular protein in tumor cells, but also in different ways to be secret outside the cell as a “cross-talk” tool for tumor cells and tumor microenvironment, thus playing an important role in the development of tumors, such as participating in epithelial-mesenchymal transition, regulating immune cell behavior, promoting neovascularization and so on. The mechanism of annexin secretion in the form of extracellular vesicles and its specific role is still unclear. This paper summarizes the main role of annexin secreted into the extracellular space in the form of extracellular vesicles in tumorigenesis and drug resistance and analyzes its possible mechanism.
Keywords: tumorigenesis